STUDI TENTANG PRESTASI BELAJAR PAI ALUMNI TK-TPA PADA SISWA SMP PESANTREN PUTRI AL-MANAWWARAH DESA PANYILI KEC. PALAKKA KAB. BONE - Hasbullah, Hasbullah; Suhra, Sarifa (Institut Agama Islam Negeri (IAIN) Bone, 2021)
AbstractThis research is a field research with the type of qualitative research. Analyzing and researching the sources of respondents found directly in the field through the results of interviews, observations and documentation. Data sources in this study are primary obtained in the field and secondary which is supporting data. Research approaches include pedagogical, psychological and sociological. Data analysis using descriptive qualitative, the aim is to systematically describe the facts obtained from the research that took place on the object. Data was processed by using data reduction, data display and drawing conclusions. The results of this study indicate that learning achievement in Islamic Religious Education subjects between the alumni of the Qur'an education park and not the alumni of the Qur'an education park shows a difference. The ability of Alquran Education Park alumni in understanding and knowing Islamic Religious Education subjects is quite profound. The depth of religious understanding from an early age has implications for students' ability to attend Islamic Religious Education lessons. The strategy used in improving student achievement in Islamic Religious Education is based on standard rules that are run by students. Its nature is education based on direct practice by students.